Reference quality genome sequence of Indian pomegranate cv. ‘Bhagawa’ (Punica granatum L.) - Roopa Sowjanya, P.; Shilpa, Parashuram; Patil, Goudappa Prakash; Babu, Dhinesh Karuppannan; Sharma, Jyotsana; Sangnure, Vipul R.; Mundewadikar, Dhananjay M.; Natarajan, Purushothaman; Marathe, Arvind Rajiv; Reddy, Umesh K.; Singh, Vikram Nripendra (Frontiers in Plant Science, 2022)
Pomegranate is an important fruit crop for ensuring livelihood and nutrition security in fragile semi-arid regions of the globe having limited irrigation resources. This is a high-value, nutritionally rich, and export-oriented agri-commodity that ensures high returns on investment to growers across the world. Although, it is a valuable fruit crop but has received only a limited genomics research outcome. To fast-track the pomegranate improvement programme, de novo whole-genome sequencing of the main Indian cultivar ‘Bhagawa’ was initiated by the Indian Council of Agricultural Research - National Research Centre on Pomegranate (ICAR-NRCP). We have demonstrated that a combination of commercially available technologies from Illumina, PacBio, 10X Genomics, and BioNano Genomics could be used efficiently for sequencing and reference-grade de novo assembly of the pomegranate genome. The research led to a final reference-quality genome assembly for ‘Bhagawa’ of 346.08 Mb in 342 scaffolds and an average N50 of 16.12 Mb and N90 of 1088.62 Kb. This assembly covered more than 98% of the estimated pomegranate genome size, 352.54 Mb. The LTR Assembly Index (LAI) value of 10 and 93.68% Benchmarking Universal Single-Copy Orthologs (BUSCO) completeness score over the 1440 ortholog genes of the completed pomegranate genome indicates the quality of the assembled pomegranate genome. Furthermore, 29,435 gene models were discovered with mean transcript length of 2954 bp and mean coding sequence length 1090 bp. Four transcript data samples of pomegranate tissues were mapped over the assembled ‘Bhagawa’ genome, up to 95% significant matches, indicating the high quality of the assembled genome. We have compared the ‘Bhagawa’ genome with the genomes of the pomegranate cultivars ‘Dabenzi’ and ‘Taishanhong’. We have also performed whole-genome phylogenetic analysis using Computational Analysis of Gene Family Evolution (CAFE) and found that Eucalyptus grandis and pomegranate diverged 64 (60-70) million years ago. About 1573 protein-coding resistance genes identified in the ‘Bhagawa’ genome were classified into 32 domains. In all, 314 copies of miRNA belonging to 26 different families were identified in the ‘Bhagawa’ genome. The reference-quality genome assembly of ‘Bhagawa’ is certainly a significant genomic resource for accelerated pomegranate improvement.